HUBUNGAN KONDISI SANITASI LINGKUNGAN RUMAH TANGGA DENGAN KEBERADAAN JENTIK VEKTOR DENGUE DI DAERAH RAWAN DEMAM BERDARAH DENGUE KOTA DUMAI TAHUN 2008 - Zulkarnaini Zulkarnaini; Yusni Ikhwan Siregar; Dameria Dameria (Jurnal Ilmu Lingkungan, 2009)
Dumai is area endemic of Dengue disease (DBD) with condition of environmental sanitary ingeneral has not well. Purpose of this research is to know image of condition of environmentalsanitary in Kota Dumai and sees are there the relation of condition of household area sanitarywith existence larvae of vector dengue and area sanitary aspect what which most dominantrelated to existence larvae of vector dengue in disease gristle area of Kota Dumai. This researchis research type of observasional with planning "Cross Sectional". Research subject ishousehold 102 households who live in gristle DBD. Sampling is done in" random sampling"Research independent variable is condition of household area sanitary covering aspect: supplyof cleanness water, management of garbage and practice of eradication of mosquito dengue.Research dependent variable is existence larvae of vector dengue. Result of analysis univariatshows condition of household area sanitary in general is unfavourable (62,7%). Out of 555containers contains water which are positive larvae at is 186 containers (33,51%). Result ofanalysis Rank Spearman shows there is relationship signifikan between condition of householdarea sanitary with existence larvae at (Rho = Rho=0,586 and p=0,000). While result ofregression analysis shows area sanitary aspect that is most dominant related to existence tolarvae at is practice of household in PSN-DBD with P value 0,000 and correlation value =0,635. Equally, factor that is very significant of existence larvae at vector dengue is PSN-DBD.